Porcine small intestine submucosal grafts improve remucosalization and progenitor cell recruitment to sites of upper airway tissue remodeling. Issue 10 (1st June 2018) - Nayak, Jayakar V.; Rathor, Aakanksha; Grayson, Jessica W.; Bravo, Dawn T.; Velasquez, Nathalia; Noel, Julia; Beswick, Daniel M.; Riley, Kristen O.; Patel, Zara M.; Cho, Do‐Yeon; Dodd, Robert L.; Thamboo, Andrew; et al.
Abstract : Background: To better understand upper airway tissue regeneration, the exposed cartilage and bone at donor sites of tissue flaps may serve as in vivo "Petri dishes" for active wound healing. The pedicled nasoseptal flap (NSF) for skull‐base reconstruction creates an exposed donor site within the nasal airway. The objective of this study is to evaluate whether grafting the donor site with a sinonasal repair cover graft is effective in promoting wound healing. Methods: In this multicenter, prospective trial, subjects were randomized to intervention (graft) or control (no graft) intraoperatively after NSF elevation. Individuals were evaluated at 2, 6, and 12 weeks postintervention with endoscopic recordings. Videos were graded (Likert scale) by 3 otolaryngologists blinded to intervention on remucosalization, crusting, and edema. Scores were analyzed for interrater reliability and cohorts compared. Biopsy and immunohistochemistry at the leading edge of wound healing was performed in select cases. Results: Twenty‐one patients were randomized to intervention and 26 to control. Subjects receiving the graft had significantly greater overall remucosalization ( p = 0.01) than controls over 12 weeks. Although crusting was less in the small intestine submucosa (SIS) group, this was not statistically significant ( p = 0.08). There was no overall effect on nasal edema ( p = 0.2). Immunohistochemistry demonstrated abundant upper airway basal cell progenitors in 2 intervention samples, suggesting that covering grafts may facilitate tissue proliferation via progenitor cell expansion. Conclusion: This prospective, randomized, controlled trial indicates that a porcine SIS graft placed on exposed cartilage and bone within the upper airway confers improved remucosalization compared to current practice standards.